Shark Attack - O'Dell, Kathryn (NewYork Cambridge University, 2014)
Sharks aren t always as vicious as the ones you see in films! Explore the myths and and learn the facts about the ocean s most famous resident.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Pre-Intermediate Level; Animals